Cadmium exposure affects iron acquisition in barley (Hordeum vulgare) seedlings. Issue 4 (23rd May 2014) - Astolfi, Stefania; Ortolani, Maria R.; Catarcione, Giulio; Paolacci, Anna R.; Cesco, Stefano; Pinton, Roberto; Ciaffi, Mario
<x xml:space="preserve">Abstract</x> This study addresses the question of the interference between iron (Fe) nutrition and cadmium (Cd) toxicity at the level of growth performance, phytosiderophores (PS) release, micronutrient accumulation and expression of genes involved in Fe homeostasis in barley seedlings, a plant with strategy II‐based response to Fe shortage. Cd exposure induced responses similar to those of genuine Fe deficiency also in Fe‐sufficient plants. Most genes involved in PS biosynthesis and secretion (HvNAS3, HvNAS4, HvNAS6, HvNAS7, HvNAAT‐A, HvDMAS1 and HvTOM1) induced by Fe deprivation were also significantly upregulated in the presence of Cd under Fe sufficient conditions. Accordingly, the enhanced expression of these genes in roots under Cd exposure was accompanied by an increase of PS release. However, induced expression of HvIRO2 and the downregulation of HvIDEF1 and HvIRT1, after Cd exposure, suggested the presence of a pathway that induces HvIRO2‐mediated PS biosynthesis under Cd stress, which probably is not simply caused by Fe deficiency. The downregulation of HvIRT1 and HvNramp5 may represent a protective mechanism at transcriptional level against further Cd uptake by these transporters. These results likely indicate that Cd itself may be able to activate Fe acquisition mechanism in an Fe‐independent manner.